'Do you think you're at the Gresham?': Accepting Imperfection in 'The Dead'. Issue 2 (July 2015) - Saloman, Randi
<x xml:space="preserve">Abstract</x> Dublin's Gresham Hotel, where Gabriel and Gretta Conroy end their evening in Joyce's most famous short story, has a fascinating history. It was founded in 1817 by Thomas Gresham, who began life as a foundling rescued from the steps of London's Royal Exchange and was thereby given the name of the Renaissance statesman who built that exchange. This sixteenth-century Thomas Gresham was even better known, however, for his eponymous 'Gresham's Law'. Both Gresham's Law and the hotel setting and history enter into and help to shape 'The Dead'. Questions of value and valuing suggested by Gresham's Law are shown to be more complicated than they initially appear, as they intersect with the various forms of hospitality traced in the story. The 'secondary' quality of the famous Dublin hotel (built by the second, unknown Thomas Gresham) underscores – and ultimately redeems – the theme of secondariness that runs through 'The Dead'.